Genetic variation for outcrossing among Caenorhabditis elegans isolates - Teotónio, H (2010)
The evolution of breeding systems results from the existence of genetic variation and selective forces favoring different outcrossing rates. In this study we determine the extent of genetic variation for characters directly related to outcrossing, such as male frequency, male mating ability, and male reproductive success, in several wild isolates of the nematode Caenorhabditis elegans. This species is characterized by an androdioecious breeding system in which males occur with hermaphrodites that can either self-fertilize or outcross with males. We find genetic variation for all characters measured, but also find that environmental variation is a large fraction of the total phenotypic variance. We further determine the existence of substantial genetic variation for population competitive performance in several laboratory environments. However, these measures are uncorrelated with outcrossing characters. The data presented here contribute to an understanding of male maintenance in natural populations through their role in outcrossing.